Pengaruh Inflasi, Pengangguran, Dan Jumlah Penduduk Terhadap Pertumbuhan Ekonomi Di Provinsi Banten Pada Tahun 2014-2023 - Diah Aska Sholeah; Duha Latifah Sari; Dwi Wijayanti; Emi Erfiana; Muhammad Kurniawan (Journal Economic Excellence Ibnu Sina, 2024)
This research aims to analyze the influence of inflation and unemployment rates on economic growth in Banten Province. The data used is annual data from 2014-2023. A quantitative approach is used using regression analysis to test the relationship between the independent variables (inflation and unemployment rate) and the dependent variable (economic growth). The results of the analysis show that inflation and the unemployment rate have a significant influence on economic growth in Banten Province. These findings have important implications in the formulation of regional economic policies to manage inflation and reduce unemployment levels to encourage sustainable economic growth in the region.